2019
DOI: 10.3126/jnspoi.v3i2.30885
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Phosphatase Levels Before and After Nonsurgical Periodontal Therapy

Abstract: Introduction: Chronic periodontitis is a multifactorial disease resulting in the inflammation and destruction of the supporting structures. Early detection of periodontal changes, prognosis and efficacy of treatment have been monitored by Alkaline Phosphatase Levels (ALP) levels. Objective: This study was carried out to determine level of ALP in saliva and serum before and after periodontal therapy. Methods: This pretest posttest study included 22 patients with generalised chronic periodontitis (GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In addition interventional studies are also necessary to examine the potential benefits of periodontal treatment. 26 If the consequences of treatment had been included in the study, it would have been more effective. Further longitudinal studies can be recommended.…”
Section: Discussionmentioning
confidence: 99%
“…In addition interventional studies are also necessary to examine the potential benefits of periodontal treatment. 26 If the consequences of treatment had been included in the study, it would have been more effective. Further longitudinal studies can be recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Pradhan et al found significantly increased salivary as well as serum ALP levels in generalised chronic periodontitis patients and after two months of non-surgical periodontal therapy significant reduction was seen in salivary ALP levels; however, no significant reduction was seen in serum ALP levels after two months 29. This might have occurred as serum ALP level depends on function of other organs as well such as bone, kidney, liver, etc.…”
mentioning
confidence: 98%